Ray Tracing Analysis For Wireless Propagation - Filzah Hanis Hairudin, Filzah Hanis (Universiti Teknolgi Petronas, 2010)
This report discusses the progress done of the chosen topic, which is Ray Tracing Analysis For Wireless Propagation. The objectives of the project are to develop MATLAB code using Ray Tracing Analysis for Wireless Propagation in the jungle and also to be able to analyze specific problems using Ray Tracing Analysis and the code developed. The developed code will also be used in comparison to another graph in a journal written by Wilbur R. Vincent [1]. Propagation in the jungle may be difficult due to multilevel canopy and the foliage that has been the cause of scattering of VHF radio waves. Ray-tracing method will be used with the aid of MATLAB-based calculation to analyze the problems on those situations. The usage of Graphical User Interface (GUI) can help to visualize the path of the ray. This will increase the efficiency of calculation and reduce the time taken for computing